1994
DOI: 10.1073/pnas.91.26.12505
|View full text |Cite
|
Sign up to set email alerts
|

One subspecies of the red junglefowl (Gallus gallus gallus) suffices as the matriarchic ancestor of all domestic breeds.

Abstract: The noncoding control region of the mitochondrial DNA of various gallinaceous birds was studied with regard to its restriction fragment length polymorphism (RFLP) and sequences of the first 400 bases. Tandem duplication of the 60-base unit was established as a trait unique to the genus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
192
1
10

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 313 publications
(210 citation statements)
references
References 10 publications
4
192
1
10
Order By: Relevance
“…It is assumed that all breeds of the domesticated chicken descend from a single ancestor, the RJF, which originated in Southeast Asia [5,14,15]. Since populations at the centre of origin should contain the highest diversity (as has been shown for humans and other species [2]), RJF should present a high level of polymorphism and also hold low values of MGD.…”
Section: The Chicken Ancestor and The Need For Conservationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is assumed that all breeds of the domesticated chicken descend from a single ancestor, the RJF, which originated in Southeast Asia [5,14,15]. Since populations at the centre of origin should contain the highest diversity (as has been shown for humans and other species [2]), RJF should present a high level of polymorphism and also hold low values of MGD.…”
Section: The Chicken Ancestor and The Need For Conservationmentioning
confidence: 99%
“…Additionally, private alleles of the domesticated breeds may indicate a contribution of other wild species as debated in Crawford [5]. In studies on the mitochondrial DNA in chickens [14,15], the authors suggest that Gallus gallus gallus could have given rise to the diverse breeds of the domesticated chicken, even though common patterns in domesticated breeds and in G. g. spadiceus and G. g. bankiva are also observed.…”
Section: The Chicken Ancestor and The Need For Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…Red Junglefowl still commonly exist in their native habitats (Brickle et al., 2008; Brisbin, 1995) and are clearly distinguishable from domestic chickens (Johnsgard, 1999). Although genetic contributions from multiple Junglefowl species may have played a role in the domestication process (Eriksson et al., 2008; Nishibori, Shimogiri, Hayashi, & Yasue, 2005), archeological and genetic evidence (Fumihito et al., 1994, 1996; Gongora et al., 2008; Storey et al., 2012; Thomson et al., 2014) indicate that Red Junglefowl from Southeast Asia was the primary progenitor of all domestic breeds of modern chickens. In a previous study, we identified substantial haplotype variation in the major histocompatibility complex (MHC) B‐locus of wild Red Junglefowl (Fulton et al., 2016; Nguyen‐Phuc, Fulton, & Berres, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Most, if not all, recent genetic studies involving junglefowl, however, sample birds from captive colonies (e.g., Berthouly et al., 2009; Eriksson et al., 2008; Fumihito et al., 1994; Gering, Johnsson, Willis, Getty, & Wright, 2015; Mekchay et al., 2014; Moiseyeva, Romanov, Nikiforov, Sevastyanova, & Semyenova, 2003; Romanov & Weigend, 2001; Rubin et al., 2010; Tadano et al., 2008; Worley et al., 2010) or from vaguely described geographic localities (e.g., Akaboot, Duangjinda, Phasuk, Kaenchan, & Chinchiyanond, 2012; Granevitze et al., 2007; Liu et al., 2006; Miao et al., 2013; Nishibori et al., 2005; Okumura et al., 2006; Ulfah et al., 2016). Even the female Red Junglefowl individual used for the Gallus gallus reference sequence (International Chicken Genome Sequencing Consortium, 2004) is traceable to the San Diego Zoo, itself believed to be introgressed with White Leghorn alleles (M. E. Delany, University of California, Davis, CA, personal communication).…”
Section: Introductionmentioning
confidence: 99%